Nie potrafię rozwiązać równań
-2(x-1)+4(2+x)=3-5x
3x-(4-x)=2(x+1)-5


Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

Zobacz obrazek Anka1355

Odpowiedź:

-2 ( x-1) + 4 ( 2+x) = 3-5x

   -2x +2 + 8 +4x= 3-5x

  -2x +4x +5x = 3 -2 -8

      7x= -7  /:7

    x= -1

spr...   -2*(-1) +2 +8 +4*(-1)= 3- 5 *(-1)

           2+2 +8-4 = 3 +5

              8-8

                  L=P

3x - ( 4 -x) = 2 ( x+1) -5

       3x  -4 +x  = 2x +2-5

     3x +x -2x= 2 -5 +4

     2x= 1 /:2

    x= 1/2

  spr..   3*1/2 -4 +1/2 = 2*1/2+2-5

  3/2 +1/2 -4= 1 +2-5

        4/2- 4= -2

       2-4= -2

         -2=-2

          L=P

Szczegółowe wyjaśnienie: